Design and analysis of an efficient photovoltaic energy-powered electric vehicle charging station using perturb and observe MPPT algorithm - Awad, Mohamed; Ibrahim, Ahmed M.; Alaas, Zuhair Muhammed; El-Shahat, Adel; Omar, Ahmed I. (Frontiers in Energy Research, 2022)
According to the current directive, we must rely on green energy for sustainable mobility. One of the green transition's goals is to use renewable energy to charge electric vehicles (EVs). Solar energy is a form of these renewable energy sources, and it is classified as being clean, available, and renewable because it is based on sunshine. The world is now turning to EVs which have lower running costs and cleaner environments. Lithium-ion batteries are employed to store energy in EVs. This paper covers the design and analysis of a photovoltaic (PV) system to charge five models of electric cars like BMW i3 2019, Volkswagen e-Golf, Fiat 500e, Mercedes EQA 250, and Hyundai Kona Electric in a DC fast charging mode, using a buck converter to minimize the volt output and applying Perturb & Observe (P&O) Maximum Power Point Tracking (MPPT) to get the extreme power and efficiency from solar panels. The charging time was calculated for each electric car of the five models in the State of Charge (SOC) area at 20 to 80 percent. By using the MATLAB program to simulate all the systems, calculate the efficiency of the MPPT controller, time of charging, and Characteristic of voltage and current levels for each model of these EVs, which tested under the condition of Irradiance level is 1000 W/m2 and temperature is 25 ℃, obtained the effective, economic of a PV system as stand-alone to charge EVs in a rapid charge mood.